Bank regulation, lending and patenting: Evidence from the EBA capital exercise - Jan Krzyzanowski; Uwe Walz (Leibniz Institute for Financial Research SAFE, 2021)
We analyze the impact of decreases in available lending resources on quantitative and qualitative dimensions of firms' patenting activities. We thereby make use of the European Banking Authority's capital exercise to carve out the causal effect of bank lending on firm innovation. In order to do so we combine various datasets to derive information on firms' financials, their patenting behaviors, as well as their relationships with their lenders. Building on this selfgenerated dataset, we provide support for the "less finance, less innovation" view. At the same time, we show that lower available financial resources for firms lead to improvement in the qualitative dimensions of their patents. Hence, we carve out a "less finance, less but better innovation" pattern.
Keywords: D22; G30; G31; G38; N24; O31; O34; 330; financing; bank lending; patents